The Body between Nature/Culture Debates from a Feminist Perspective - Nahhas, Hanayeh; Shomar, Towfic (Jordan Journal of Social Sciences, 2021)
We can easily claim that the body is the dominator to all the feminists’ movement globally. The issue of the body (women embodiment in particular) have overshadowed the feminist thought throughout the last three decades, the women emancipation is interwoven with her body’s freedom: what she wears , her looks, her role to bread, commercializing her, and violence against her are all related to her being in a female body. The science-feminism relation never was a happy one; sciences usually advocating a certain ideology to support specific roles of men and women. The critic addressing such ideological perception of sciences highlights the importance of the cultural in sciences, and how such perception influence the images and social fabric these sciences presents. Hence, it is essential to be able to explore the influence of these theories on our perception. New materialistic view has an important project that puts it in direct conflict with the said replies to the feminists’ critics, through making “the material (the material human body) and the natural world at the upfront of feminists’ practices and theories.” We are tackling such discussions from the most general question of “what does it means to understand humans as part of nature and how would we be able to think of nature stemming from being part of it?” connecting such feminists’ discussions with Merleau – Ponty’s philosophy. We suggest that Merleau – Ponty’s prospective of our bodies as representative of the world, would shack the nature/culture dualism and unite the body with the world. The thinking-body theory would not be able to eliminate the nature/culture debate; nonetheless, it would pave the way to think deeply into the trilogy of nature/culture/body as part of one structural knowledge.